The Role of Economic Activities of Sahaba (R.A) in the Evolution of Islamic Culture: An Analysis - Dr. Muhammad Arfan (DIRAYAT, 2024)
The life of Prophet Muhammad (peace be upon him) is the ultimate standard for Muslims. He as well as all his teachings, theoretical & practical, were a role model for mankind. He introduced a din(religion) where isolation was prohibited. He established a state to lead the universe where besides other requirements, economic stability was indispensable. An economically self-sufficient state has the full strength to dominate others. His Sahaba(R.A) engaged themselves in different economic activities, trading, agriculture, dairy farming, gardening, crafting, goldsmithing, blacksmithing, carpentry, tailoring, laboring, etc., by obeying him. These traders and skilled persons exported their traditions, morals, and culture to other states with their products. Muslims were the first nation to permit others to adopt their traditions and culture. This step made the revolution in world history because ancestor-ruling civilizations (Grecian, Roman, Persian) did not allow other nations to adopt their traditions. In this article, the economic activities of sahaba(R.A) have been studied and analyzed that how these activities developed the Islamic culture.